Desarrollo de un acumulador cinético electromagnético autopropulsado. (2022)
Generators and energy accumulators are gaining great importance in the modern world, thanks to their ease of producing and accumulating energy. However, due to the intermittency of renewable energy sources, there is often an energy deficit and at other times excess, so it is necessary to accumulate that excess to be used in the moments of deficit. This project aims to develop an electromagnetic kinetic accumulator of permanent magnets of axial and radial flow, in order to solve the problem presented above. For the design, simulation and proper assembly of each piece, the Autodesk Inventor program was used, Later the pieces were made in the 3D printer, except for the axis and the radial stator. The expected result was a working prototype of a laboratory-scale electromagnetic kinetic accumulator. with the work done a functional prototype of a radial and axial flow accumulator generator was obtained, due to the material used and its small size, the generator works, but the accumulation is not achieved. The conclusions of this work is that it is technically feasible to build an axial-radial generator accumulating kinetic energy, which has the possibility of accumulating excess kinetic energy and converting it into electrical energy at times of deficit of the motor source